Response-independent environmental changes and their interaction with verbal reports. (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The present study investigated the effects of exposure to both controllable and uncontrollable aversive events on the performances of adults. A second goal was to evaluate the effects of requests for verbal reports on participants' performances. Forty adults were assigned to 3 groups: participants of the Escape Group were exposed to a Training Condition where an aversive sound could be turned off by their responses. Participants of the Yoked Group were exposed to the same Training Condition, but no responses were effective in turning off the sound. Participants of all Groups were exposed to a Test Condition where a different response turned off the sound. Participants of the Escape and Yoked Groups were assigned to 1 of 3 verbal report conditions where they were asked if they knew how to turn off the sound in given trials. Results did not suggest effects associated with helplessness or superstitious behavior, but specific patterns of responding to the Training Condition were closely related to participants' performances in the Test Condition. Results showed that the verbal reports did not contribute to the emergence or prevention of helplessness.
Keywords: Verbal report; Contingency; Contiguity; Learned helplessness; Superstitious behavior